2004
DOI: 10.1124/jpet.104.068635
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid 2-Arachidonylglycerol Decreases the Immunological Activation of Guinea Pig Mast Cells: Involvement of Nitric Oxide and Eicosanoids

Abstract: The antigen-induced release of histamine from sensitized guinea pig mast cells was dose-dependently reduced by endogenous (2-arachidonylglycerol; 2AG) and exogenous [(1R,3R,4R)-3-[2-hydroxy-4-(1,1-dimethylheptyl)phenyl]-4-(3-hydroxypropyl)cyclohexan-1-ol (CP55,940)] cannabinoids. The inhibitory action afforded by 2AG and CP55,940 was reversed by N- [(1S)-endo-1,3,3-trimethylbicyclo[2.2.1]heptan-2-yl]5-(4-chloro-3-methylphenyl)-1-(4-methylbenzyl)pyrazole-3-carboxamide (SR144528), a selective cannabinoid 2 (CB 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 39 publications
2
31
1
Order By: Relevance
“…Similar effects of indomethacin were obtained in dogs in vivo, where the anaphylactic coronary contraction was considerably diminished (39). These results may supplement the classical point of view that the main mediators of anaphylaxis eliciting the peak contraction to the antigen are histamine or/and serotonin (4,8). The interactions between their effects and the effects of cyclooxygenase products may be complicated, and unfortunately, there is almost no clear evidence of these interactions.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Similar effects of indomethacin were obtained in dogs in vivo, where the anaphylactic coronary contraction was considerably diminished (39). These results may supplement the classical point of view that the main mediators of anaphylaxis eliciting the peak contraction to the antigen are histamine or/and serotonin (4,8). The interactions between their effects and the effects of cyclooxygenase products may be complicated, and unfortunately, there is almost no clear evidence of these interactions.…”
Section: Discussionmentioning
confidence: 52%
“…The main possible cause of hypotension is the release of mediators of anaphylaxis, following the IgE hypersensitivity reaction. Vasoactive substances such as histamine (1)(2)(3)(4), serotonin (5-7), and bradykinin (5,8) are well-recognized mediators of cardiac anaphylaxis. The antigenic stimulation of sensitized tissues is associated also with the release of slow-reacting substance of anaphylaxis (SRS-A), which mainly consists of systemic vasoconstrictors leukotrienes -LTD, LTC, and LTE (9, 10) -as well as thromboxane and endothelin (11).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacologic (such as short-term bronchodilation) [21] and immunomodulatory effects [22, 23] of C. sativa -derived cannabinoids could favor the mildness of symptoms. In fact, 60% of the symptomatic patients were current smokers in spite of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, application of CB1 and CB2 agonists and antagonists to rat peritoneal mast cells did not affect histamine release (62). In another study, 2-arachidonoylglycerol and CP55,940 decreased mast cell activation by being susceptible to a CB2 antagonist and inhibition of nitric oxide and prostanoid pathways (63). In the present study, CB2 expression was not observed in groups 1 and 4, but it was observed in groups treated with CYP.…”
Section: Discussionmentioning
confidence: 44%